Assistance to Business Actors Through the Cultivation of Grapefruit Seeds to Improve the Village Economy - M. Abi Mahrus Ubaidillah; Dian Erwanto; Achmad Baidowi; Moh. Tamim Ngizamul Ngulya; Muhammad Rizky Gymnastiar; Muhamad Maftuh (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
This community service activity aims to increase the capacity of village business actors in the agribusiness sector through the transfer of knowledge and skills in the cultivation of sustainable and high economic value grapefruit seeds. The approach used is the Asset-Based Community Development (ABCD) method, which focuses on local potential and assets. These steps include: local potential, determination of goals and expectations, program design, determination of direction and indicators of success, and implementation and sustainability. This activity involved the village community and the owner of PT. Rumawan Pusaka Negeri as a partner. The results of the activity showed an increase in the knowledge and skills of residents in the seeding and grafting techniques of grapefruit seedlings, the formation of a new farmer group